Use of audiovisual documentation in the daily reports of Canal Extremadura TV - Blanco-Izquierdo, María Jesús; Caldera-Serrano, Jorge (Revista General de Información y Documentación, 2012)
The results of a study conducted at Extremadura TV Channel are shown in this paper, discussing the use of information held by the Department of Documentation. It is shown through a careful analysis both the thematic material required by journalists and the ratio of broadcasted material that has been extracted from the archives. The format of images requested by journalists as well as their geographic coverage is also discussed has been used mainly archival material.